The importance and availability of adjustments to improve access for autistic adults who need mental and physical healthcare: findings from UK surveys - Ann Le Couteur; Jeremy R Parr; Colin Wilson; Samuel Brice; Jacqui Rodgers; Barry Ingham; David Mason; Mark Freeston (BMJ Open)
Objectives To investigate autistic people’s views on the importance and availability of adjustments to mental and physical healthcare provision. To explore whether specific categories of adjustments can be identified and to identify any differences in their importance and availability between mental and physical healthcare.Design Data from two studies, both employing a cross-sectional survey design.Setting UK-based autistic adults registered with the Adult Autism Spectrum Cohort-UK were contacted by post or online. In both studies, recruitment was staged over a 12-month period. Non-responders were sent a single reminder letter 2 weeks after initial contact.Participants 537 autistic adults completed a survey about mental health services (51% response rate), 407 completed the physical health survey (49% response rate). Within these samples, 221 participants completed both surveys.Primary outcome measures Each study developed a bespoke survey to explore participants’ views on mental and physical health services, respectively. Both included an identical list of adjustments that participants rated based on importance and availability.Results Three factors of important adjustments were identified: sensory environment, clinical and service context, and clinician knowledge and communication. Adjustments across healthcare settings were widely rated as being important yet rarely available. One significant difference between the importance of adjustments available through mental and physical health services was identified. Participants reported that having access to a clinician who is willing to adapt their approach to suit the person’s preferences was significantly more important for participants attending mental health settings (p=0.001).Conclusions Autistic people reported the limited availability of important adjustments in current healthcare provision. To address unmet need and tackle the health inequalities faced by autistic people attending physical and mental healthcare settings, healthcare providers should offer adjustments relating to the three identified factors. Future research should focus on identifying and addressing service provider barriers to implementation.